Dear Mr. Blueberry - James, Simon, 1961- (New York : M.K. McElderry Books : Maxwell Macmillan International Pub. Group, 1991)
A young girl and her teacher correspond about the whale she has discovered in her pond.
Keywords: Whales -- Fiction; Letters -- Fiction